Counter‐ion Effect on Micellization of Ionic Surfactants: A Comprehensive Understanding with Two Representatives, Sodium Dodecyl Sulfate (SDS) and Dodecyltrimethylammonium Bromide (DTAB). Issue 5 (9th February 2013) - Naskar, Bappaditya; Dey, Arnab; Moulik, Satya P.
Abstract: Various micelle parameters viz., critical micelle concentration (CMC), counter‐ion binding ( β ), aggregation number ( N ), hydrodynamic radius ( R h ), micelle zeta potential ( ζ ) and energetic parameters, free energy of micellization ( G m 0 ), enthalpy of micellization ( H m 0 ) and entropy of micelle formation ( S m 0 ) were determined for sodium dodecylsulfate, and dodecyltrimethylammonium bromide in the presence of NaCl for the former and NaBr for the latter. Conductometry and calorimetry methods were used for the measurements of CMC and energetic parameters. The fluorimetric (static quenching) method was employed to determine N and dynamic light scattering to estimate R h and ζ . The conductometrically determined β was verified from the CMC values by calorimetry using the Corrin–Harkins equation. The results found for the two surfactants of identical tails but different head groups have been presented and discussed. A detailed report on the salt effect using salts containing counter‐ions the same as those in the surfactant is found only limitedly in the literature.